Bastroe Canal and the Convention on Environnemental Impact Assessment in a Transboundary Context (ESPOO Convention) - Ichim, Oana Andreea (Journal of Danubian Studies and Research, 2023)
In order to ensure an environnemental governance, the transparency of the decisions that implies the impact transboundary on the environnement should be guaranteed. Therefore, the Convention on environnemental impact assessment in a transboundary context, so called the EPSOO Convention, offers the necessary means for the signatory parties to evaluate the impact for the activities at a very incipient stade of planification. Moreover, it forces those parties to notify and consult each other on the activities which could have a negative impact on the environnement. Besides this convention, there is also a strategic Protocol which requires to the parties to anticipe the negative consequences and that the decision should be made having into consideration those negative aspects. Despite a consolidated international legal framework in terms of prevention, the construction project and the maintenance of the Bâstroe canal, a waterway Danube - Black Sea, arouses interest at national and international level. We aim to analyze if Ukraine has respected the international ecological binding clauses in order to avoid an negative impact on the environnement, above all in Danube Delta ecosystem. Thereby, we analyze the importance of this canal for Ukraine, the position of the Romanian authorities and that of the international community.